Digital Readiness as Driver of Sustainable Organizational Performance in Higher Education Institution: Systematic Literature Review - Yustinus Rawi Dandono; Indra Siswanti; Lenny Christina Nawangsari; Mafizatun Nurhayati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Growing demand on higher education institutes (HEIs) to consider digital transformation and sustainability at the same time has raised interest among scholars in digital readiness as a strategic driver for sustainable long-term organizational performance. The purpose of this study is therefore 3-fold: First, by means of a systematic review, to synthesize what we know about how digital readiness is defined and understood in the context of HEIs. Adopting a systematic literature review (SLR) design and guided by PRISMA 2020, this investigation analyzed 96 high-quality articles between bellwether year, 2015 to prognostic year of interest 2025. A thematic synthesis was carried out to explore the predominant patterns, mechanisms and theorizing of the digital readiness–performance link. Findings Five interdependent themes are brought to light: (1) digital readiness as a strategic capability, (2) governance and data-driven readiness enabling evidence-based sustainability, (3) human and cultural readiness in the guise of mediating mechanisms, (4) technological and infrastructural readiness propelling operational sustainability, and finally (5) digital leadership and strategic alignment as catalysts. The synthesis shows that the digital readiness is more than just about technological readiness, and include institutional capabilities that promote efficiency, resilience, innovation and governance legitimacy. In the absence of appropriate compendium, this study has gone a step forward by combining RBV DCs and sustainability to produce an integrated theoretical framework that offers new insights on both theory and practice for HEI leaders and their policy makers in search of sustainable digital transformation.